(x-2y+z)(-x+2y+z)

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/17 13:52:38
(x-2y+z)(-x+2y+z)
xݒ[K@ǿKHf24SI9*3[l'A-.,/VE/EWeLRv *w}v3KN]F )t,ץq`5N%_I~=?zͤKoMt4VXFLzScE,Z!i2ʿB,çstw頻R`$[Q(TD,a"ƮR[FyC:aYo2ŗhX9oq͉87q+j,|Z 2]ϦU͝_ N/BxPcѢC1Uf0)V"V1)cb4lBM#ʂ/P`Q%^َ.DݍlES„S20^mpG0B }_O{̨G0?٭IʢCW%4lz

(x-2y+z)(-x+2y+z)
(x-2y+z)(-x+2y+z)

(x-2y+z)(-x+2y+z)
等我去拿草稿纸

=z^2-(x-2y)^2
=z^2-(x^2-4xy+4y^2)
=z^2-x^2+4xy-4y^2
祝你学习进步,希望采纳我的回答,谢谢

(z+(x-2y))(z-(x-2y))=z^2-(x-2y)^2=z^2-(x^2-4xy+4y^2)=z^2-x^2-4y^2+4xy

收起

-(x-2y+z)(x-2y+z)=(x-2y)^2-z^2=